The Role of Ultrasound Across the Inflammatory Arthritis Continuum: Focus on “At-Risk” Individuals - Duquenne, Laurence; Chowdhury, Rahaymin; Mankia, Kulveer; Emery, Paul (Frontiers in Medicine, 2020)
In individuals at-risk of developing inflammatory arthritis, the value of an ultrasound assessment to predict disease progression has been demonstrated repeatedly. However, at-risk individuals may be identified and assessed at different stages in the arthritis continuum, therefore representing a heterogeneous population. As a consequence, the predictive value of an ultrasound assessment may differ between cohorts. In this review, we discuss the use of ultrasound in the different at-risk populations across the inflammatory arthritis disease continuum.This review demonstrates that US has been used more frequently in at-risk individuals with symptoms compared with asymptomatic at-risk populations. The data suggests, ultrasound is most useful in three at-risk populations: those with a positive ACPA test in the context of non-specific MSK symptoms, those with clinically suspect arthralgia and those with palindromic rheumatism. The predictive value of an ultrasound assessment suggests it will be a cornerstone of risk prediction modelling and prevention studies of inflammatory arthritis in the future.